Is there persistence in the impact of emergency food aid?: Evidence on consumption, food security, and assets in rural Ethiopia - Gilligan, Daniel O.; Hoddinott, John F. (Wiley, 2007)
The primary goal of emergency food aid after an economic shock is often to bolster short-term food and nutrition security. However, these transfers also act as insurance against other shock effects, such as destruction of assets and changes in economic activity, which can have lasting deleterious consequences. Although existing research provides some evidence of small positive impacts of timely food aid disbursements after a shock on current food consumption and aggregate consumption, little is known about whether these transfers play a safety net role by reducing vulnerability and protecting assets into the future. We investigate this issue by exploring the presence of persistent impacts of two major food aid programs following the 2002 drought in Ethiopia: a food-for-work program known as the Employment Generation Schemes (EGS) and a program of free food distribution (FFD). Using rural longitudinal household survey data collected in 1999 and 2004, we estimate the impact of these programs on consumption growth, food security, and growth in asset holdings 18 months after the peak of the drought, when food aid transfers had substantially or entirely ceased in most program villages... Overall, these results suggest that emergency food aid played an important role in improving welfare, access to food, and food security for many households following the drought in 2002. However, improved targeting, especially in EGS, and larger, sustained transfers may be required to increase benefits, particularly to the poorest households. The impacts of food aid identified here indicate some persistence or accumulated effects of transfers on consumption growth over time. Although the time lag between receipt of transfers and observed consumption is not more than one year in most cases, the estimated impact on consumption growth relative to the size and timing of transfers suggests possible savings or multiplier effects of emergency food aid.